Delavier's women's strength training anatomy workouts - Delavie, Frederic; Gundill, Michael (Anatomy series (Human Kinetics (Organization)), 2015)
Based on the anatomical features unique to women, this guide sets the standard for women's strength training. It features full-colour illustrations that allow readers to see inside 40 exercises and 42 programmes for strengthening, sculpting and developing arms, chest, back, shoulders, abs, legs and glutes.